2019
DOI: 10.1021/acs.jafc.9b00837
|View full text |Cite
|
Sign up to set email alerts
|

Pocket-based Lead Optimization Strategy for the Design and Synthesis of Chitinase Inhibitors

Abstract: Insect chitinases play an indispensable role in shedding old cuticle during molting. Targeting chitinase inhibition is a promising pest control strategy. Of ChtI, a chitinase from the destructive insect pest Ostrinia furnacalis (Asian corn borer), has been suggested as a potential target for designing green pesticides. A 4,5,6,7-tetrahydrobenzo­[b]­thiophene-3-carboxylate scaffold was previously obtained, and further derivatization generated the lead compound 1 as Of ChtI inhibitor. Here, based on the predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 25 publications
(38 reference statements)
0
36
0
Order By: Relevance
“…Furthermore, a pocket-based lead optimization based on compound 11 was performed, and several compounds with improved inhibitory activity were obtained. 29 Among them, compound 12 with a 6-tert-pentyl substituent inhibited Of ChtI, with a K i value of 0.71 μM. The binding mode of compound 12 is similar to the mode observed in compound 11, but the larger steric hindrance at the 6nonpolar group of compound 12 enhanced interactions with the surrounding amino acids.…”
Section: Development Of Small Molecules Targeting Insect Chitinasesmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, a pocket-based lead optimization based on compound 11 was performed, and several compounds with improved inhibitory activity were obtained. 29 Among them, compound 12 with a 6-tert-pentyl substituent inhibited Of ChtI, with a K i value of 0.71 μM. The binding mode of compound 12 is similar to the mode observed in compound 11, but the larger steric hindrance at the 6nonpolar group of compound 12 enhanced interactions with the surrounding amino acids.…”
Section: Development Of Small Molecules Targeting Insect Chitinasesmentioning
confidence: 86%
“…Molecular docking studies revealed that they occupied subsites from −3 to +1 via hydrophobic stacking interactions with aromatic residues, including Tyr30, Trp34, Phe61, Trp107, Tyr272, Phe309, and Trp372 (Figure D). Furthermore, a pocket-based lead optimization based on compound 11 was performed, and several compounds with improved inhibitory activity were obtained . Among them, compound 12 with a 6- tert -pentyl substituent inhibited Of ChtI, with a K i value of 0.71 μM.…”
Section: Development Of Small Molecules Targeting Insect Chitinasesmentioning
confidence: 99%
“…If chitin digestion and degradation in the old cuticle are hindered, insect growth and development will be blocked [ 10 ]. The key genes that affect insect molting are potential insect control targets [ 6 , 7 , 44 ]. HEXs are enzymes involved in chitin catabolism during insect growth [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crop pests pose a serious challenge to agricultural production and food security [ 1 , 2 ]. As such, target-based insecticides have high specificity and safety to non-target organisms and the environment; thus, they have attracted considerable attention [ 3 , 4 , 5 , 6 , 7 , 8 ]. Chitin is a long-chain polymer of N -acetylglucosamine that is present in many insect tissues including the epidermis, integument, trachea, salivary gland, and intestinal peritrophic membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The scarce nematode chitinase inhibitors may be, to a great extent, attributed to the lagged research on the structure of nematode chitinases. The availability of structure information could facilitate both structure-based virtual screening for inhibitor development and elucidation of inhibitory mechanism for inhibitor optimization [24][25][26][27] . Recently, we resolved the crystal structure of CeCht1 (PDB ID: 6LDU), a chitinase from the model nematode C. elegans 28 .…”
Section: Introductionmentioning
confidence: 99%